The role of the Caliph Al-Nasser of Deenullah in the Mongol invasion of the Islamic state - حمودي, شيرين; حسن , غادة; احمد, حنان (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The era of the Abbasid Caliphate is one of the historical, political and civilization Eras in the history of Muslims. In fact the Abbasid era is not just an Islamic era in history, but is along period in The Islamic history includes centuries successive replete with important events and Phenomena in History of the Islamic nation, including the Mongol invasion, which Was one of the massive waves of destruction that be fell humans before the stone In a country that was alive. There were many opinions about why the Mongols came to the land of Islam, One Was that Caliph Al-Nasser was responsible and accused of colluding with the Mongols, in order to get rid of some of the forces that rebelled against the caliphate And threatened their property represent end by the state algorithm. However, this Charge needs to be verified to verify its authentioned in the primary sources, with Will be addressed, analyzed and criticized to reach as much as possible to its Authenticity.